'Toys for Reconciliation': A Grassroots Peacebuilding Initiative in Bucaramanga, Colombia. Issue 1 (2nd January 2018) - Anctil Avoine, Priscyll; Bolívar Durán, José Fabián
Abstract: In a grassroots effort to counter the institutional and state-centred narratives on disarmament, demobilisation, and reintegration (DDR) processes conceptualised by the Integrated DDR Standards of the United Nations, the NGO Corporación Descontamina has organised local projects around what it has identified as significant problems in previous work carried out in a Bucaramanga men's jail where ex-paramilitaries and ex-guerrilleros live together. In fact, two main problems have been observed: the socioeconomic and emotional situation of the ex-combatants, preventing their reintegration, and the social stigmatisation surrounding their return to civil society. As such, drawing upon decolonial theory, the objective of this article is to present the peacebuilding project 'Toys for Reconciliation' that was developed by Corporación Descontamina with the aim of advancing reconciliation in the context of the Colombian armed conflict.